A hobbyist looks at Zulu and Xhosa songs - Swartz, J. F. A. (International Library of African Music, 1956)
My interest in Bantu songs was that of the singer. I wanted Bantu songs to sing and to teach others to sing. I have not developed the ethnologist's interest in Bantu songs. I have, in other words, not concerned myself with the folklore aspect of Bantu songs. It was development from the primitive to Bantu songs of today that intrigued me. I have, for myself, made three very interesting discoveries. The first is that the language of the Southern Bantu, particularly Xhosa which I have studied, is a wonderful language of song. I have come to regard it as second to none in this respect. I shall return to this point presently. My second discovery was the range of Bantu songs from the point of view of development, or should I say, levels of development. My third discovery follows on because it concerns the host of Bantu song-writers in the Eastern Cape, particularly. I was amazed to find so many educated Xhosas and Zulus, trying their hand at song writing.
Keywords: South Africa; Composers; Ethnomusicology; Songs; Zulu (African people); Xhosa (African people); Eastern Cape; African Music